When recommending a product backfires: The effects of justification and source on user responses to online personalized recommendations - Laurie BALBO*; Florence JEANNOT; gnès HELME-GUIZON (Systèmes d'information et management, 2022)
Providing users with personalized product or service recommendations has undergone considerable development with the advent of Web 2.0. Recommendations allow websites to convey tailored information to users, but they also contribute to reduce the users’ efforts at searching online. Despite corporate enthusiasm for online personalized recommendations, some previous investigations have demonstrated that this practice requires precautions in order to avoid potential counterproductive effects. This research aims at better understanding the boundaries conditions under which the justification for product recommendations displayed on a website are needed. It compares the effects of justification when a recommendation is issued by the previously navigated website or by a partner website. According to the Construal Level Theory, the navigated website is a proximal source while the partner website is a distal source of recommendation. Through a full-factorial experimental design with 328 participants, this study assesses the interaction between justification (justified vs not-justified) and source (proximal vs distal) of a recommendation. Results reveal that on the one hand a recommendation delivered by a proximal source is more persuasive if the recommendation is justified than if it is not-justified. On the other hand, for a distal source, superior effects are achieved if no justification is provided. Perceived intrusiveness is the underlying mechanism of these effects